2021
DOI: 10.13073/fpj-d-20-00069
|View full text |Cite
|
Sign up to set email alerts
|

Orthotropic Viscoelastic Properties of Chinese Fir Wood Saturated with Water in Frozen and Non-frozen States

Abstract: In order to better understand the differences in orthotropic viscoelastic properties of Chinese fir (Cunninghamia lanceolata) in frozen and non-frozen states, the storage modulus (E′) and loss modulus (E″) of the longitudinal, radial, and tangential specimens were investigated under water-saturated conditions with temperatures ranging from −120°C (or 30°C) to 280°C. Results revealed that the order of magnitude in E′ for each orientation was consistent for temperatures below 0°C, while the anisotropy in E′ was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…These findings indicate that the drying rate of free water has less effect on collapse for samples with a length below 200 mm. When the MC is lower than the FSP, the collapse of the 30 and 100 mm samples had a small change, but the collapse of the 200 mm samples increased to a peak after the MC reached the FSP and subsequently deceased with MC reducing due to the recovery of cell walls [41]. The differences of final shrinkage of three sets of samples were not great in this study.…”
Section: Wood Shrinkage and Collapsecontrasting
confidence: 50%
See 1 more Smart Citation
“…These findings indicate that the drying rate of free water has less effect on collapse for samples with a length below 200 mm. When the MC is lower than the FSP, the collapse of the 30 and 100 mm samples had a small change, but the collapse of the 200 mm samples increased to a peak after the MC reached the FSP and subsequently deceased with MC reducing due to the recovery of cell walls [41]. The differences of final shrinkage of three sets of samples were not great in this study.…”
Section: Wood Shrinkage and Collapsecontrasting
confidence: 50%
“…The transversal shrinkage curves of the samples during the drying are shown i ure 7. Generally, normal shrinkage occurs at an MC below the FSP [41]. However, al ples shrink both in the tangential and radial direction above the FSP.…”
Section: Wood Shrinkage and Collapsementioning
confidence: 99%
“…Finally, the energy attenuation rate along the samples at the end of the drying process (after 160 days) can be calculated as the sum of the difference between the initial and final state of EMC, from the pith to the outmost layers of the sample. Analytically, this can be expressed using Equation (6), where β is the coefficient of the energy attenuation rate.…”
Section: Equilibrium Moisture Content Model and The Acoustic Emission...mentioning
confidence: 99%
“…Specifically, Scots pine shows a density that ranges between 505 kg/m 3 and 540 kg/m 3 when the moisture content is varied between 12% and 12.4% [5]. Indeed, recently, Li et al demonstrated that moisture content has a direct effect on the mechanical properties of wood by modifying orthotropic viscoelastic performance during a water loss process [6], and other recent studies assessed that this change in the mechanical behaviour of wood leads to differences in energy release for acoustic emission monitoring during fracture when moisture content changes [7,8]. Indeed, fluctuations in ambient relative humidity (RH) are considered the main factor that contributes to the deterioration of wooden objects and acoustic emissions are able to detect the stress induced by such climate variability [9].…”
Section: Introductionmentioning
confidence: 99%